Craniofacial growth and development of Turner syndrome children - Sasmita, Inne Suherna; Pertiwi, Arlette Suzy Puspa; Achmad, M Harun (Universitas Padjadjaran, 2009)
Turner syndrome is a genetic disorder which characterized by specific physical appearance and the lost of one of sex chromosome in females. The most frequent chromosome constitution in Turner syndrome is 45X. This disorder may cause an interruption of growth and development in the whole body as well as in the craniofacial region. The oral manifestations of Turner syndrome are micrognathia, high palate, malocclusion, and the premature eruption of first permanent molars. This paper will discuss the oral manifestations associated with the craniofacial growth and development of Turner syndrome.